No woman, no kraj; Girls just to wanna have choice, czyli o intertekstualności haseł umieszczanych na transparentach w czasie Strajku Kobiet jesienią 2020 roku - Sokół-Klein, Anna (Przegląd Środkowo-Wschodni, 2022)
The purpose of the article is to conduct a linguistic analysis of the slogans which appeared on the banners during women’s strike in autumn 2020. The linguistic characteristics of a selected group of slogans (referring to literature, film, music and political affairs) is preceded with a typology of all slogans used by the demonstrators. The source material was obtained from newspapers (Nasz Dziennik, Dziennik Trybuna, Dziennik Łódzki, Gazeta Wyborcza, Gazeta Polska, Newsweek Polska, Angora, Express ilustrowany, Dziennik Gazeta Prawna) and the social media (Michal Rusinek’s profile, as well as pages “Wydarzenia w Łodzi” and “Łodź” on Facebook) between October 23rd and November 11th, 2020. The selected examples are characterized in terms of their intertextuality (most intertextual games are also a basis for slogans tinged with humour) and the linguistic creativity of the authors.